IMPACT OF DEMOCRATIC LEADERSHIP STYLE ON JOB PERFORMANCE OF SUBORDINATES IN ACADEMIC LIBRARIES IN PORT HARCOURT, RIVERS STATE, NIGERIA - Dolly C, Kalu; Nonyelum P., Okpokwasili (International Journal of Research -GRANTHAALAYAH, 2018)
The study focused on the influence of democratic leadership style on job performance of subordinates in academic libraries in Port Harcourt, Rivers State, Nigeria. The research design adopted for the study was a survey, while the 74 professional and para-professional staff working in the libraries studied were the respondents. Data collection was through questionnaire instrument titled “Democratic Leadership Style on Job Performance of Subordinates in Academic Libraries (DLSJPSAL)” made up of of five (5) item statements. Research question was answered using frequency counts, total score and means. Findings of the study revealed that democratic leadership style in academic libraries studied has positive influence on subordinates’ job performance because it results in high employees’ productivity. This style of leadership tends to have work groups that were very productive and subordinates showed a high degree of satisfaction on the job. Among others, the researchers recommended that heads of academic libraries should be encouraged to adopt democratic leadership style since it yields higher result in job performance of subordinates and consequently to users’ satisfaction with library services.